PENGEMBANGAN APLIKASI ANTI-BULLYING UNTUK MENGATASI BULLYING DI SEKOLAH BERBASIS PENDEKATAN PSIKOLOGIS - Zarina Akbar; Murti Kusuma WIrasti; Maratini Shaliha Aisyawati; Devia Sokaarru Ristindra; Qurotta Aini; Elsha Cahyani Fadli (Jurnal Edukasi : Jurnal Bimbingan Konseling, 2021)
Bullying is an oppressive behavior carried out repeatedly by perpetrators who areusually stronger than the victims and it often has negative impacts on both the perpetratorsand the victims. Cases of bullying in schools are increasing every year, indicating that thecurrent handling of the problem of bullying has not been comprehensive and complete. Inbullying situations, apart from perpetrators and victims, there are also other roles in it,namely observers. Often, the handling or prevention of bullying is more focused on victimsand perpetrators, even though the third parties have the possibility to play an important rolein preventing bullying. Most bullying prevention programs are only directed at theperpetrators and victims of bullying. In this article, the authors propose an anti-bullyingapplication for junior high school students, named antibully. id. This application providespsychological-based bullying education and prevention programs for perpetrators, victims,and observers of bullying. The programs in the application are expected to be able to help thetrauma recovery process for victims, help perpetrators manage their emotions, and educateobservers about bullying behavior to reduce bullying cases in schools.